The Predictive Value of ΣΔST/ΔHR Index for Restenosis after Percutaneous Coronary Intervention - Kim, Chul (Korean Academy of Rehabilitation Medicine, 2012)
OBJECTIVE: To find out the predictive value of the ΣΔST/ΔHR index for restenosis after percutaneous coronary intervention (PCI). METHOD: Subjects of this research were patients who participated in a cardiac rehabilitation (CR) program as six to eight weeks of a hospital-based program after receiving PCI to treat acute coronary syndrome (ACS). The patients received coronary angiography (CAG) at the onset of the ACS and nine months after that, and also received an exercise tolerance test (ETT) at the start of the CR program and several days before receiving a follow-up CAG. In ETT, we used the sum of the ST depression (ΣΔST index) of leads II, III, aVF, V(4-6) as well as the sum of the ΔST/ΔHR (heart rate) (ΣΔST/ΔHR index) in the same leads and the sum of the ΔST/ΔRPP (rate pressure product) (ΣΔST/ΔRPP index) in the same leads. We compared the predictive power of each index of ETT for restenosis after PCI. RESULTS: The sensitivity, specificity, positive predictive value, and negative predictive value of ΣΔST index were 69%, 47%, 31%, and 82%. The ΣΔST/ΔHR index was 13.7±5.2 in the restenosis group and 9.3±5.6 in the patent group (p=0.017). The sensitivity, specificity, positive predictive value, and negative predictive value of this index were 85%, 63%, 44%, and 92%. The ΣΔST/ΔRPP index were 0.10±0.08 in the restenosis group and 0.06±0.04 in the patent group (p=0.016). The sensitivity, specificity, positive predictive value, and negative predictive value of this index were 54%, 76%, 44%, and 83%. CONCLUSION: The ΣΔST/ΔHR index showed a much higher sensitivity and negative predictive value for restenosis after PCI compared to the ΣΔST index.